Smart Mind Control Drone - Oripov Shoxruxmirzo Muzaffarbek ugli (Genius Journals, 2022)
Small pilot machines that can do everything in this article. When I had the opportunity to do a project with great technology, I was determined to make the dream of the world come true by driving a drone with your mind.
Keywords: Smart mind Control Drone; PCB; Parts list; Notices